Influence of Reactant Vibrational Excitation on Stereodynamics of C + NO → CN + O Reaction (Journal of Atomic and Molecular Sciences, 2016)
Stereodynamics of the title reaction at different reagent vibrational states(v=0-2) are obtained using the quasiclassical trajectory method at collision energy of0.06 eV on an accurate $^4A"$ potential energy surface. The vector properties includingangular momentum $P(θ_r)$ and $P(φ_r)$ distributions as well as polarization-dependentdifferential cross sections (PDDCS) of the product CN are presented. Furthermore,the influence of vibrational excitation on the product vector properties has also beenstudied in present work.
Keywords: stereodynamics; vibrational excitation; quasiclassical trajectory.